Introduction to flight testing - Gregory, James W.; Liu, T. (Tianshu); Ohio Library and Information Network (Hoboken, NJ : Wiley, 2022)
"Flight testing as the final stage of the aircraft design cycle is very important in aerospace industries. Flight testing involves various engineering disciplines such as aeronautical, mechanical, electrical and structural aspects all together, forming a technical discipline itself. Although flight testing plays an important role in the design of aircraft, it is typically not included in the traditional aeronautical engineering curriculum. Few universities offer such a course, due in part to the high cost of maintaining and operating a fully-instrumented experimental aircraft for flight testing. This book promotes the use of modern, off-the-shelf instruments such as MEMS devices to collect necessary data for flight testing on non-experimental general aviation aircraft. This new development eliminates the need for specialized aircraft for instruction of flight testing"--
BIBINDX
Keywords: Airplanes -- Flight testing -- Textbooks; Electronic books; Textbooks; Textbooks